Hubungan Pelaksanaan Inisiasi Menyusu Dini (IMD) Dan Faktor Sosiodemografi Ibu Dengan Keberhasilan Pemberian ASI Eksklusif Pada Bayi Usia 6-11 Bulan Di Wilayah Kerja Puskesmas Baki Sukoharjo - Utami, Mayaningtyas Esya; , Kusuma Estu Werdani, SKM., M.Kes (2017)
Breast milk is the best food, and the main source of nutrition for newborns until baby of six months. Ministry of Health report in 2015, exclusive breastfeeding coverage in Indonesia by 55.7%, and from report Sukoharjo Health Office by 60.4%. Health Center of Baki included in three subdistricts in Sukoharjo with low exclusive breastfeeding coverage from 2014 to 2015. This coverage is still below the national target of 80%. A preliminary study in the working area health centers Baki shows that 8 out of 10 mothers surveyed have not conducted exclusive breastfeeding. The purpose of this research was to analyze the relationship of implementation initiation of early breastfeeding and sociodemographic factors with the success of exclusive breastfeeding in babies aged 6-11 months in the working area health centers Baki Sukoharjo. This type of research is observational with cross sectional approach. Sample of this research is mothers who have babies aged 6-11 months in the working area Health Center of Baki were 95 people, with proportional random sampling technique. The statistic test technique used Chi-square. The results showed are not relation among the the implementation initiation of early breastfeeding (p=0.321) with exclusive breastfeeding. In sociodemographic factors, variabel of age (p=0.088), education (p=0.925), and parity (p=0.920) also showed no association, while variables of mother working status (p=0.049) indicated there was association with exclusive breastfeeding in babies age 6-11 months in the working area health centers Baki Sukoharjo.